Introduction to the special issue: evidence in the intimate sphere - Chin, Jason M.; Douglas, Heather; Goss, Caitlin (Current issues in criminal justice, 2020)
We are pleased to introduce this special issue dealing with the complex and interlocking web of evidence issues that arise in intimate partner violence (IPV) cases. Set against the backdrop of a global pandemic, rolling stay-at-home orders and immense economic uncertainty, many signs point to domestic violence being on the rise in Australia and abroad. While we could not have foreseen these circumstances, we hope these articles -which arose from a workshop held at the Queensland Supreme Court in December 2019 ('Crime in the Intimate Sphere: Issues in Evidence')-can provide some insights into an often understudied component of intimate partner violence (besides this Issue, the slides from that workshop are available online, https://osf.io/v4cfx/).